Cortical Plasticity Induced by Anodal Transcranial Pulsed Current Stimulation Investigated by Combining Two-Photon Imaging and Electrophysiological Recording - Ma, Zengguang; Du, Xiaolang; Wang, Feifei; Ding, Ran; Li, Yuanyuan; Liu, Aili; Wei, Liangpeng; Hou, Shaowei; Chen, Feng; Hu, Qi; Guo, Cunle; Jiao, Qingyan; et al. (Frontiers in Cellular Neuroscience, 2019)
Anodal-transcranial pulsed current stimulation (a-tPCS) has been used in human studies to modulate cortical excitability or improve behavioral performance in recent years. Multiple studies show crucial roles of astrocytes in cortical plasticity. The calcium activity in astrocytes could regulate synaptic transmission and synaptic plasticity. Whether the astrocytic activity is involved in a-tPCS-induced cortical plasticity is presently unknown. The purpose of this study is to investigate the calcium responses in neurons and astrocytes evoked by a-tPCS with different current intensities, and thereby provides some indication of the mechanisms underlying a-tPCS-induced cortical plasticity. Two-photon calcium imaging was used to record the calcium responses of neurons and astrocytes in mouse somatosensory cortex. Local field potential (LFP) evoked by sensory stimulation was used to assess the effects of a-tPCS on plasticity. We found that long-duration a-tPCS with high-intensity current could evoke large-amplitude calcium responses in both neurons and astrocytes, whereas long-duration a-tPCS with low-intensity current evoked large-amplitude calcium responses only in astrocytes. The astrocytic Ca2+ elevations are driven by noradrenergic-dependent activation of the alpha-1 adrenergic receptors (A1ARs), while the intense Ca2+ responses of neurons are driven by action potentials. LFP recordings demonstrated that low-intensity a-tPCS led to enhancement of cortical excitability while high-intensity a-tPCS resulted in diminution of cortical excitability. The results provide some evidence that the enhancement of a-tPCS-induced cortical excitability might be partly associated with calcium elevation in astrocytes, whereas the diminution of a-tPCS-induced cortical excitability might be caused by excessive calcium activity in neurons. These findings indicate that the appropriate current intensity should be used in the application of a-tPCS.